DEVELOPMENT OF AN IOT-BASED AUTOMATED DRIP IRRIGATION AND FERTIGATION SYSTEM FOR CHILI FARMING IN ARID REGIONS OF EAST JAVA - Fujita, Miku; Nakamura, Yui; Tanaka, Kaito (Techno Agriculturae Studium of Research, 2025)
Chili farming in arid regions of East Java faces persistent challenges related to water scarcity, inefficient irrigation practices, and inconsistent nutrient managment, which negatively affect crop productivity and farmers’ livelihoods. Traditional irrigation methods often result in excessive water use and uneven fertilizer distribution, limiting plant growth and increasing production costs. Recent advances in Internet of Things (IoT) technology offer promising solutions for precision agriculture by enabling automated, data-driven irrigation and fertigation systems tailored to specific crop and environmental conditions. This study aims to develop and evaluate an IoT-based automated drip irrigation and fertigation system designed for chili farming in arid areas of East Java. The system is intended to optimize water and nutrient usage while improving crop growth and resource efficiency. The research adopts a research and development (R&D) approach combined with experimental field testing. The system integrates soil moisture sensors, temperature and humidity sensors, nutrient solution controllers, and an IoT microcontroller connected to a cloud-based monitoring platform. The system was tested in selected chili farms over one growing season, with performance evaluated based on water consumption, fertilizer efficiency, plant growth indicators, and yield outcomes. The results indicate that the IoT-based system reduced water usage by approximately 30% and fertilizer consumption by 25% compared to conventional irrigation methods. Chili plants managed under the automated system showed more uniform growth, improved plant health, and a yield increase of 20%. Farmers also reported improved ease of irrigation management and real-time monitoring capabilities. The study concludes that IoT-based automated drip irrigation and fertigation systems are effective in enhancing water efficiency, nutrient management, and chili crop productivity in arid regions. The system demonstrates strong potential for supporting sustainable agriculture and climate-resilient farming practices in East Java.